2013
DOI: 10.1007/s13277-013-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases in cancer: their value as diagnostic and prognostic markers and therapeutic targets

Abstract: Biomarkers are used as tools in cancer diagnostics and in treatment stratification. In most cancers, there are increased levels of one or several members of the matrix metalloproteinases (MMPs). This is a family of proteolytic enzymes that are involved in many phases of cancer progression, including angiogenesis, invasiveness, and metastasis. It has therefore been expected that MMPs could serve as both diagnostic and prognostic markers in cancer patients, but despite a huge number of studies, it has been diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
244
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(255 citation statements)
references
References 111 publications
5
244
1
5
Order By: Relevance
“…Other matrix metalloproteinases, such as MMP-1 and MMP-7, similarly to MMP-9 exhibit proteolytic activity towards ECM, and these two enzymes also correlate with an aggressive phenotype of colorectal cancer [Hadler-Olsen et al, 2013]. Our study is the fi rst report on the inhibition of MMP-1 expression by the evening primrose polyphenol extract in a colon cancer cell line.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Other matrix metalloproteinases, such as MMP-1 and MMP-7, similarly to MMP-9 exhibit proteolytic activity towards ECM, and these two enzymes also correlate with an aggressive phenotype of colorectal cancer [Hadler-Olsen et al, 2013]. Our study is the fi rst report on the inhibition of MMP-1 expression by the evening primrose polyphenol extract in a colon cancer cell line.…”
Section: Discussionmentioning
confidence: 61%
“…Except for neutrophils, cells do not accumulate MMPs. After synthesis, MMPs are secreted into the ECM as a latent form that can be activated by either proteolytic cleavage or by conformational changes induced, among others, by reactive oxygen species (ROS) [Hadler-Olsen et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…PT93 was reported as a selective MMP inhibitor, inhibiting MMP-2 and MMP-9 (22). A number of studies demonstrated that MMPs are associated with the ability of tumors to migrate and invade (12,26,27). First generation MMPIs with broad-spectrum MMP inhibitory ability cause unexpected side effects, including musculoskeletal pain and inflammation (12,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of MMP-2 and MMP-9 were observed in high-grade gliomas compared with non-invasive low-grade astrocytoma and normal brain tissue (4,10). In the 1990s, following the identification of the important role of MMPs in cancer angiogenesis, growth and metastasis, MMPs became a therapeutic target for cancer treatment, which determined interest in the design and evaluation of matrix metalloproteinases inhibitors (MMPIs) as anticancer agents (11,12). MMPs have been revealed to be important in regulating cellular activities and are involved in physiological and pathological processes (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation